A Reconstruction of Time of Money Towards The Economic Value of Time for Islamic Finance - Muhammad Akhyar Adnan, Muhammad (FE UMY, 2014)
the conventional finance. However, it is also suspected by many that the TVM has also coloured strongly the Islamic finance in practices. It is why a continuous criticism on this issue is unstoppable till present. Academically, there is also a discourse about the Economic Value of Time (EVT). It is believed that this concept is more acceptable from Islamic point of view. This paper is a theoretical in nature. It tries to analyse and discuss the possibility of reconstruction of the Islamic Finance by transforming the concept of Time Value of Money into Economic Value of Time. Based on various arguments and perspectives, we believe that the concept of TVM can be reconstructed and transformed into the concept of EVT. Having more acceptable concept in Finance, it is believed that Islamic Financial Institutions may grow faster and be more acceptable by both Muslim societies particularly and other societies generally. In turn, the Islamic financial institutions can be replacing the conventional financial institutions which are complained not to be not fair enough since they apply the usurious concept which prohibited by Islam and other main religions in this world.